Leading edge marketing : turning technology into value - Williams, Veronica A., (2014 digital library., 2014)
Leading Edge Marketing was inspired by the response to several of my articles and speeches, notably The Five Ps of Marketing (www.The5Ps .com). This book is a comprehensive blueprint of the concepts presented in the article. Leading Edge Marketing is intended for anyone who wants to learn how to identify, create, and deliver a hi-tech product or service that will be purchased by a critical mass of people. It presents the techniques and end-to-end process to produce a profit from products and services. The essence of my book is that it takes old principles, updates them to the current environment, adapts them to technology, and, most importantly, explains how they can be put to work to deliver respectable market share and strong profits...with integrity. Leading Edge Marketing is a comprehensive guide to deliver a winning solution--from concept to profit. Reprinted with permission from The5Ps.com.